Communication Patterns Between Leaders and Employees in Improving Performance - Nurmitasari, Ainy Amiranti; Karnay, Sudirman; Farid, Muhammad; Saleh, Nurming (Interference: Journal of Language, Literature, and Linguistics, 2024)
Abstract. This study aims to ascertain the impact of communication patterns and leadership styles on enhancing employee performance. The research was conducted at the Faculty of Language and Literature, Makassar State University. This research is a qualitative study that employs questionnaires and interviews as data collection techniques. The research data were analyzed using the Miles and Hubermann model, encompassing data collection, reduction, presentation, and conclusion drawing. The findings revealed that leaders at the Faculty of Language and Literature, Makassar State University, employed various communication strategies. In general, the communication patterns used by leaders encompass vertical, horizontal, and diagonal communication patterns among leaders, leaders to subordinates, and subordinates to leaders. The data indicates that persuasive, participatory, listening, and transformational communication styles exert a considerable and beneficial influence on employee performance. The combination of leadership communication patterns and styles positively impacts employee performance, including in the processes of discussing and planning a work program, as well as in coordination and decision-making. Positive relationships between leaders and employees are associated with a higher employee work ethic. It can be surmised that leadership communication patterns and styles have a markedly beneficial effect on employee performance and can improve their work performance. The barriers to the interaction between leaders and employees are differences in perception, organizational culture, use of technology, and lack of communication skills. Keywords: Leadership Communication Patterns, Employee Performance, Organizational Communication, Communication Barriers